Impact of cancer screening on metastasis: A prostate cancer case study. (December 2021) - Lange, Jane; Remmers, Sebastiaan; Gulati, Roman; Bill-Axelson, Anna; Johansson, Jan-Erik; Kwiatkowski, Maciej; Auvinen, Anssi; Hugosson, Jonas; Hu, Jim C; Roobol, Monique J; Carlsson, Sigrid V; Etzioni, Ruth
Background: Trials of cancer screening present results in terms of deaths prevented, but metastasis is also a key endpoint that screening seeks to prevent. We developed a framework for projecting overall (de novo and progressive) metastases prevented in a screening trial using prostate cancer screening as a case study. Methods: Mechanistic simulation model in which screening shifts a fraction of cases that would be metastatic at diagnosis to being non-metastatic. This shift increases the incidence of non-overdiagnosed, organ-confined cases. We use estimates of the risk of metastatic progression for these cases to project how many progress to metastasis after diagnosis and tally the projected de novo and progressive metastatic cases with and without screening. We use data on stage shift from the European Randomized Study of Screening for Prostate Cancer (ERSPC) and data on the risk of metastatic progression from the Scandinavian Prostate Cancer Group-4 trial. We estimate the relative risk and absolute risk reductions in metastatic disease at diagnosis and compare these with reductions in overall metastases. Results: Assuming no effect of screening beyond initial stage shift at diagnosis, the model projects a 43% reduction in metastasis at diagnosis but a 22% reduction in the cumulative probability of metastasis over 12 years in favor of screening. These results are consistent with the empirical findings from the ERSPC. Conclusion: Any reduction in metastatic disease at diagnosis under screening is likely to be an overly optimistic predictor of the impact of screening on overall metastasis and disease-specific mortality.